Multinodular and vacuolating neuronal tumour of the cerebrum: a rare neuroimaging incidentaloma or a potentially treatable cause of focal epilepsy?. Issue 2 (30th April 2019) - Baščarević, Vladimir; Pejović, Aleksa T.; Ristić, Aleksandar J.; Vojvodić, Nikola; Raičević, Savo; Đukić, Tijana; Brajković, Leposava; Sokić, Dragoslav
ABSTRACT: Multinodular and vacuolating neuronal tumour (MVNT) of the cerebrum is a relatively new, well defined histopathological and neuroradiological entity, in many cases associated with an early adult‐onset epilepsy. These lesions have an indolent course and resemble both malformative and neoplastic processes, combining a focal developmental anomaly and a low‐grade tumour. Herein, we report a case of a 48‐year‐old female patient with left temporal lobe epilepsy associated with MVNT. In addition, a comprehensive review of all the previously published cases is provided with a focus on seizure‐related cases, surgical treatment, and postoperative outcome.